2016
DOI: 10.5114/fn.2016.62554
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the expression of KAI1/CD82 and PDGFRβ and their impact on glioma progression

Abstract: A b s t r a c t The biological features of glioma cells may define their clinical outcome. Little is known about the interactions between KAI1/CD82 metastatic suppressor protein and PDGFRβ in gliomas. The aim of the study was to examine KAI1/CD82 and PDGFRβ expression in gliomas in order to find the impact of these proteins on progression of the tumors. PDGFRβ, KAI1/CD82 protein expression and mRNA of genes were evaluated on eighty four paraffin-embedded tissue of gliomas using immunohistochemical staining and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(72 reference statements)
1
0
0
Order By: Relevance
“…PDGFRs are well-characterized RTKs in GBM that have been found to be overexpressed in human gliomas of all grades, are most highly expressed in GBM, and are closely associated with GBM initiation and progression ( 20 , 28 ). Similar to previous studies ( 30 ), we observed that overexpression of PDGFRβ was a frequent event in human GBM. To the best of our knowledge, this is the first study to demonstrate that the expression levels of PDGFRβ vary and are positively correlated with the expression levels of LRIG2 in human GBM, indicating that the inter-individual variation in PDGFRβ expression may be determined by the expression pattern of LRIG2, and PDGFRβ expression may be positively regulated by LRIG2 in human GBM, which was demonstrated in vitro and in vivo in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…PDGFRs are well-characterized RTKs in GBM that have been found to be overexpressed in human gliomas of all grades, are most highly expressed in GBM, and are closely associated with GBM initiation and progression ( 20 , 28 ). Similar to previous studies ( 30 ), we observed that overexpression of PDGFRβ was a frequent event in human GBM. To the best of our knowledge, this is the first study to demonstrate that the expression levels of PDGFRβ vary and are positively correlated with the expression levels of LRIG2 in human GBM, indicating that the inter-individual variation in PDGFRβ expression may be determined by the expression pattern of LRIG2, and PDGFRβ expression may be positively regulated by LRIG2 in human GBM, which was demonstrated in vitro and in vivo in the present study.…”
Section: Discussionsupporting
confidence: 91%